The Facile Modification of Polyacrylate Emulsion via Hexadecane to Enhance Controlled-release Profiles of Coated Urea - Shen, Yazhen; Du, Changwen; Zhou, Jianmin; Ma, Fei (Scientific reports, 2018)
Development of controlled-release urea (CRU) has attracted research attention because of food scarcity problems and environmental concerns. To slow down the nutrient release of CRU coated with waterborne polyacrylate, conventional emulsion polymerization (CEP), conventional emulsion polymerization containing hexadecane (CEP + HD), and miniemulsion polymerization (MP) were carried out to discern the influence of polymerization technique and hexadecane on the properties of emulsions, films, and on the resultant nutrient release profiles of controlled-release urea. The addition of hexadecane improved water resistance, decreased the glass-transition temperature, and slowed down the nutrient release. CEP + HD was superior to MP in retarding nutrient release since the majority of HD was distributed in the exteriors of the particles of the former and interiors of the particles of the latter. Exterior HD improved water resistance more effectively, while interior HD reduced glass-transition temperature more significantly. Overall, our findings showed that incorporation of HD into polyacrylate emulsion produces excellent coatings that delay the release of urea. It has great potential application in controlled-release fertilizers coated with waterborne polymers.